Die Politik der Sowjetischen Militäradministration in Deutschland (SMAD): Kultur, Wissenschaft und Bildung 1945-1949. Ziele, Methoden, Ergebnisse. Dokumente aus russischen Archiven - Orlowa, Julia G. (Texte und Materialien zur Zeitgeschichte, 2005)
This edition provides an introduction to the wide range of policies applied in the Soviet Occupation Zone (SBZ) with respect to the areas of culture, education and science. Carefully selected and translated documents shed light on the relationship between the occupational forces and the traditions and institutions of the emerging German Democratic Republic. It represents the initial result of a joint German-Russian research project on the history of the SMAD made possible by the recent release of the original sources in Russian archives